Application of Singing Method to Improve Students' Understanding at Mi. Nihayatul Amal Rawamerta in Recognizing The Pillars Of Islam In The Subject of Fiqh - Winengsih, Wiwin; Hasanah, Widdatun; Hasanah, Wardatul; Widyaningsih, Wiwin (MANDAILING GLOBAL EDUKASIA, 2025)
his study aims to improve the understanding of grade 1 students of MI Nihayatul Amal Rawamerta, Karawang, in recognizing the pillars of Islam through the application of the singing method in the subject of Fiqh. Learning in grade 1 often faces obstacles in attracting students' attention, especially in understanding abstract concepts such as the pillars of Islam. The lack of variation in learning methods causes students to get bored quickly and not understand the material well. Therefore, the singing method was chosen as a fun and effective learning strategy. This study used a classroom action research (CAR) approach with two cycles, each consisting of the planning, implementation, observation, and reflection stages. Data were collected through observation, interviews, and student evaluation tests. The results showed that the application of the singing method significantly improved students' understanding of the pillars of Islam. In the first cycle, students' understanding increased by 65%, and in the second cycle it increased to 85%. In addition, students looked more enthusiastic, active, and were able to memorize the pillars of Islam faster. Thus, the singing method has proven effective in improving grade 1 students' understanding of the pillars of Islam. The use of this method also contributes to creating a more enjoyable and interactive learning atmosphere. Therefore, it is suggested that teachers integrate singing methods in learning Fiqh and other subjects to improve students' understanding.